The impact of socioeconomic deprivation on the risk of atrial fibrillation in patients with diabetes mellitus: A nationwide population-based study - Han, Minju; Lee, So-Ryoung; Choi, Eue-Keun; Park, Sang-Hyeon; Lee, HuiJin; Chung, Jaewook; Choi, JungMin; Han, Kyung-Do; Oh, Seil; Lip, Gregory Y. H. (Frontiers in Cardiovascular Medicine, 2022)
Objective: To evaluate the relationship between socioeconomic status and the risk of atrial fibrillation in patients with diabetes mellitus. Research Design and Methods: From the National Health Insurance Service database, we identified 2,429,610 diabetic patients who underwent national health check-ups between 2009 to 2012. Tracing back the subjects for five years from the date of health check-up, we determined the subjects' income and whether they received medical aid (MA) during the past five years. Subjects were divided into six groups according to the number of years of receiving medical aid (MA groups 0 through 5) and into four groups according to socioeconomic status change during the past five years. We estimated the risk of atrial fibrillation for each group using the Cox proportional-hazards model. Results: During a median follow-up of 7.2 ± 1.7 years, 80,257 were newly identified with atrial fibrillation. The MA groups showed a higher risk of atrial fibrillation than the non-MA group with the hazard ratios (HRs) and 95% confidence interval (CI) 1.32 (1.2-1.44), 1.33 (1.22-1.45), 1.23 (1.13-1.34), 1.28 (1.16-1.4), and 1.50 (1.39-1.63) for MA groups 1 through 5, respectively. Dividing subjects according to socioeconomic condition change, those who experienced worsening socioeconomic status (non-MA to MA) showed higher risk compared to the persistent non-MA group (HR 1.54; 95% CI 1.38-1.73). Conclusion: Low socioeconomic status was associated with the risk of atrial fibrillation in patients with diabetes. More attention should be directed at alleviating health inequalities, targeting individuals with socioeconomic deprivation to provide timely management for atrial fibrillation.